Terra Analytica: The Automated Gaze of Corn and Soy. - SAMSON, AUDREY; GALLARDO, FRANCISCO (Afterimage, 2023)
The article presents the discussion on analytical apparatus creates a visualization of finance capital's random-access memory, constantly updating and rewriting itself. Topics include artistic research adds to the discussion concerned with the agency of predictive systems and archives to perform the future, as well as the operationality of technological assemblages; and aesthetics produced by industrial agriculture become machine readable and compatible with the cybernetic conception of system.